Строение почек возобновления видов рода Hemerocallis L. - Крохмаль, И.И. (Промышленная ботаника, 2010)
Выявлены особенности строения почек регулярного возобновления видов рода Hemerocallis L. в условиях интродукции на юго-востоке Украины. Установлены не только различия в сроках их закладки, дифференциации, а также и в строении. Выявлено, что почки возобновления у раннецветущих видов закладываются в конце июня – начале июля, у среднецветущих – в конце августа. Установлено, что дифференциация вегетативно-генеративных почек возобновления у H. middendorfii наступает в середине сентября, у H. minor – в середине октября. Вегетативно-генеративные почки H. middendorfii к концу вегетационного периода в условиях юго-востока Украины более дифференцированы, вплоть до сформированного генеративного побега с зачатками соцветий, отдельных цветков и пыльцы в пыльниках. Peculiarities of constitution of species regular reproduction buds of the Hemerocallis L. genus in the conditions of introduction in the south-east of Ukraine have been determined. The differences not only in their terms of initiation, differentiation, but also in their constitution have been established. It has been found that reproduction buds hibernacula are initiated in late June in early July flowering species and in late August in midseason-flowering species. It has been established that differentiation of vegetative-generative reproduction buds occurs in H. middendorfii in mid September and in H. minor later, in mid October. The vegetative-generative buds of H. middendorfii are more differentiated by the end of the vegetative period in the conditions of the south-east of Ukraine, to the extent of a euformic generative bine with primordia of inflorescences, separate flowers and pollen in the anthers.